Determinasi Psikologis Auditor Terhadap Pertimbangan Profesional Auditor - Christina Christina; Fadiyah Husna Afraini (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
Auditor psychological factors may limit the auditor’s cognitive ability to make professional judgments. It shows that even though the auditor has perfomed the audit work professionally and in accordance with auditing standards, misjudgments may still occur. This research aims to determine auditors’ psychological determinant that may affect auditors’ professional judgment. Self-efficacy and skepticism are the psychological factors that will be examined for their influence on auditors’ professional judgment. This study uses Individual Psychology by Alfred Adler as grand theory to explain the relationship between variables. This is a causal study using quantitative data types and primary data sources. Auditors working at registered KAP in South Jakarta based on the directory of IAPI directory 2024 are the population of this study. The data was collected by distributing questionnaire to respondents who meet the criteria. The samples were obtained with a total of 92 samples using purposive sampling method. The data analysis method uses multiple linear regression, and then processed using IBM SPSS version 26. The results show that self-efficacy and skepticism, partially and simultaneously, have positive and significant effect on auditors’ professional judgment